Melatonin Enhances Maize Germination, Growth, and Salt Tolerance by Regulating Reactive Oxygen Species Accumulation and Antioxidant Systems - Wei-Qing Li; Jia-Yu Li; Shao-Jie Bi; Jia-Yue Jin; Zhong-Ling Fan; Zi-Lin Shang; Yi-Fei Zhang; Yan-Jie Wang (Plants)
Melatonin (MT) is a crucial hormone that controls and positively regulates plant growth under abiotic stress, but the biochemical and physiological processes of the combination of melatonin seed initiation and exogenous spray treatments and their effects on maize germination and seedling salt tolerance are not well understood. Consequently, in this research, we utilized the maize cultivars Zhengdan 958 (ZD958) and Demeiya 1 (DMY1), which are extensively marketed in northeastern China’s high-latitude cold regions, to reveal the modulating effects of melatonin on maize salinity tolerance by determining the impacts of varying concentrations of melatonin on maize seedling growth characteristics, osmoregulation, antioxidant systems, and gene expression. The findings revealed that salt stress (100 mM NaCl) significantly inhibited maize seed germination and seedling development, which resulted in significant increases in the H2O2 and O2− content and decreases in the antioxidant enzyme activity and photosynthetic pigment content in maize seedlings. However, exogenous melatonin considerably reduced the development inhibition caused by salt stress in maize seedlings. Moreover, exogenous melatonin alleviated NaCl-induced membrane damage and oxidative stress, and reduced Na+ content and excessively large quantities of reactive oxygen species (ROS). In addition, exogenous melatonin increased antioxidant enzyme activity and the expression of the antioxidant enzyme genes ZmSOD4, ZmCAT2, and ZmAPX2. This study demonstrates the potential role of combined melatonin seed initiation and foliar spray treatments in mitigating the detrimental effects of salt stress on maize growth, giving a theoretical foundation to future research on the possible advantages of exogenous regulating chemicals in attaining sustainable production in salt-alkaline soils.